Chitosan Reinforced Alginate Microcapsules Retained The Release of Papain in Simulated Gastric Fluid - C.I.S Arisanti; Rachmawati, H; Pamudji, J.S.; Sumirtapura, Y.C. (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2012)
Alginate microcapsules were obtained by emulsification/internal gelation technique was chosen as carrier papain and the potential use as an oral controlled release system investigated. Chitosan was then applied as a membrane coat to increase the mechanical and stabilize the microcapsules in simulated gastric fluid. Papain microcapsules consisted of particle size distribution, morphology, entrapment efficiency of papain in the microspheres and release study. The release study was performed in various pHs with or without proteolitic enzyme. Narrow particle size distribution with average of 315-560 µm was obtained from microcapsule prepared with water/oil ratio of 30 : 70, acid/CaCO3 molar ratio of 6 : 1 and agitation speed of 400 rpm. Papain microcapsule with that composition has entrapment efficiency of 95.79%. The release of papain from the alginate-chitosan microcapsule took place trough diffusion and relaxation of polymer at pH 1.2-4.5. The in vitro release studies showed that alginate-chitosan complex formation reduce erosion of alginate-chitosan matrix at pH 6.8. Both pepsin and pankreatin increased release of papain. Alginate-chitosan polyelectrolyte complex occurred on the surface of papain microcapsule controlled the release of papain from microcapsule. The presence of chitosan on the surface of microcapsule retained the release of papain in undesired site (gastric). In conclusion, papain microcapsule developed in this study is suggested to be appropriate approach for oral delivery of papain. Keywords: Papain; Microcapsules; Alginate, Chitosan; Pepsin; Pankreatin